Impact of physical activity on physical function and quality of life after liver transplantation - Wirkijowski, Jakub; Niegowska, Wiktoria; Gajek-Flanczewska, Wiktoria; Flanczewski, Sebastian; Wiklińska, Agata; Śliwińska, Martyna; Wójtowicz, Katarzyna; Walczak, Agata; Jaroń, Aleksandra; Piątkowska, Karolina (Quality in Sport, 2024)
Introduction and aim of the study: Liver-related diseases are very common in our society, and as a result, the number of people requiring liver transplantation is likewise increasing. In our research, we intended to analyze the topic of increasing survival rates and improving comfort along with the quality of life while waiting for a transplant, as well as in the postoperative period. We determined that we would investigate the impact of physical activity on risk factors that increase hospitalizations after surgery and decrease quality of life. We summarized the effect and type of exercise on sarcopenia, frailty, and their direct relation to the pre- and post-operative period of liver transplantation. In addition, we analyzed possible obstacles and difficulties arising from the implementation of physical activity in liver transplant recipients. Materials and methods: The authors conducted an extensive review of articles available in PubMed, Google Scholar, UpToDate, Science Direct, and Cochrane databases. The keywords liver transplantation, physical activity, quality of life, sarcopenia, and frailty were the basis of the review. Studies published between 2001 and 2024 were included in the review. Results: The vast majority of the studies emphasized the positive effects of exercise, particularly aerobic and resistance training, on improving the clinical conditions and well-being of liver transplant patients. The papers with inconsistent results nevertheless underscored the need to delve further into this topic. Thus, the overall evidence supports the inclusion of physical exercise in post-transplant care as a key strategy for improving health and quality of life. Conclusion: Regular physical activity is beneficial for clinical outcomes and patients’ quality of life after liver transplantation.